The Effect of Hadang and Bentengan Traditional Games on the Level of Physical Fitness of Students at SDN 02 Riang Bandung (Study of Literature) - Khoirudin, Muhamad; Lanos, Muhsana El Cintami; Handayani, Widya (Journal of Social Work and Science Education, 2023)
This study examines the effect of traditional games on the physical condition of elementary school children. Because of the lack of enthusiasm to move, the child looks unenthusiastic. This of course weakens the condition of students. It also weakens children's mobility and physical condition, and they get sick easily. The purpose of this study: The effect of traditional games on improving student fitness at SDN 02 Riang Bandung. One type of research is library research or often called library research. The nature of the descriptive analysis of this research is so that readers can understand it well. The data used in this study is additional data obtained from the results of research conducted by previous researchers. The data collection method used in this study is the method of recording or documentation. The data analysis used in this article is annotated bibliography analysis. Based on the literature review, it can be stated that the application of traditional games can be a solution to improve the physical fitness of elementary school children. Supporting factors are good student motivation, the role of parents and the environment, and sufficient opportunities to play.